مظاهر الإعجاز القرآني في الرسم العثماني .................................. Miraculous Features in the Uthmani Script of the Quran - بكير, فاطمة ممدوح محمد حسين (الدراسات الإسلامية, 2018)
The writer of this paper has highlighted certain rhetorical aspects of the ‘Uthmani script of the Quran. This script had been sanctioned by the Prophet SAWS in his practice and the scholars of all times have had a consensus that this was the standerd script of the Quran, the writer asserts with reference to earlier authorities. She has collected a number of significant examples from the mode of writing according to this script to illustrate her contention that the verses of the Quran written in the ‘Uthmani script provide further evidence of Quran’s miraculous status. This she has done by comparing the mode of ‘Uthmani script with other prevailing script. In the end, the writer has suggested further in-depth study of each feature of this script to bring out the hither to un-noticed miraculous features of the Quran.